Mundkur Memorial Lecture - Post-harvest Fruit Pathology -- Present Status and Future Possibilities - PATHAK, V.N. (Indian Phytopathology, 2002)
This paper was presented as the Mundkur Memorial Lecture at the 49th Annual Meeting of Indian Phytopathological Society held at R. D. Vishwavidyalaya, Jabalpur, India on February 16, 1997. The economic importance of post harvest diseases of fruits, their inoculum and transmission, infection and pathogenesis, epidemiology, disease management, eradication, integrated disease management and the directions for future research are briefly reviewed.